Corán y lengua árabe: entre el dialecto, el árabe medio y el fuṣḥà - Garduño, Moisés (El Colegio de México, 2012)
This article addresses the complex linguistic reality of Arabic, defined by diglossia or multiglossia, which involves the coexistence of the classical language or fuṣḥā, spoken dialects ('āmiya, dāriŷa or lahŷa), and "Middle Arabic" or ʿarabī al-wusṭà. The study focuses on how this diversity has profoundly influenced genesis, evolution, and expansion of the language. It also explores how despite its dialectal variants and the presence of Middle Arabic, the contemporary Arabic language exhibits a remarkable unity in terms of written language, originating largely from the foundations of linguistic studies of the fuṣḥā in the Quran.